Ekspresi P53, Bcl-2 dan Nm23-H1 pada Karsinoma Ovarium Tipe Serosum dan Musinosum serta Hubungannya dengan Stadium dan Derajat Histologi - Rusnita .; Prijono Tirtoprodjo; Irianiwati . (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2016)
Background Ovarian carcinoma is the second most common malignancy of the female genital tract, following endometrial carcinoma. Highly mortality of ovarian carcinoma is primarily due to difficulties in diagnosing early stage disease. Metastatic process is influenced by many factors, including molecular factors p53, Bcl-2 and nm23- H1. p53 is a tumor suppressor gene that acts to control cell proliferation, while Bcl-2 is an oncoprotein that inhibit apoptosis, which is also associated with response to chemotherapy. Mutation of p53 gene might inhibit Bcl-2 gene therefore stimulate cell proliferation and metastasis. nm23-H1 gene is metastatic inhibitor and decrease the level or expression of these genes will increase the risk of metastasis. p53, Bcl-2 and nm23-H1 expression of ovarian carcinoma need to be investigated in order to obtain more accurate prognosis. This study aimed to investigate p53, Bcl-2 and nm23-H1 expression in Serous and Mucinous ovarian carcinoma and to determine their association with Staging and Grading . Methods Design of this research was a cross sectional design. Subjects used in this study were 50 paraffin-embedded tissues of epithelial ovarian carcinoma, which had been taken from Dr. Sardjito General Hospital (Pathology Laboratory archive). Samples were processed with immunohistochemical staining (IHC) methode using monoclonal antibody anti p53, bcl-2, and nm23-H1. Different expression of p53, Bcl-2, nm23-H1 among samples and their association with staging and grading was analyzed with chi-square. Results p53 expression was associated with grading but not with staging of serous ovarian carcinoma and this protein was not expressed in mucinous ovarian carcinoma. Both Bcl-2 and nm23-H1 expression was not associated with grading and staging of serous ovarian carcinoma. In mucinous ovarian carcinoma, bcl-2 and nm23-H1 expression was not associated with staging. Conclusion Bcl-2 expression was not different among early stages of serous and mucinous ovarian carcinoma. nm23-H1 expression was not significantly different with grading and staging of both ovarian carcinoma. Key words : Bcl-2, mucinosum, nm23-H1, ovarian carcinoma, p53, serosum.